Assessment of the mangrove community structure in Barangay Baguingin, Tigbauan, Iloilo - Celendro, Annalisa Antillon
The term 'mangroves' refers to the number of species of trees and shrubs that are adapted to the conditions of the intertidal zone. They are found along coastal waters, tidal flats, extending along the rivers, streams and its tributaries where the water is brackish. This studygenerally aims to assess the community structure of mangroves in Barangay Baguingin, Tigbauan Iloilo. Specifically, theis study aims to: 1.) determine the physical and chemical factors such as salinity, pH, and temperature of soil and water as well as characterization of substrates; 2.) identify and classify the mangroves present in the area; and 3.) described the community structure in terms of Stand Basal Area, Stems per Hectare, Relative Density, Relative Frequency, Relative Dominance, Importance Value and Shannon Index of Diversity. The mangrove area was studied using the transect line plot method., A total of twelve true mangrove species were present in the area. These were Avicennia alba, Avicennia marina, Avicennia rumphiana, Lumnitzera racemosa, Exoecaria agallocha, Algeceras floridum, Nypa fruiticans, Bruguiera cylindrica, Rhizophora apiculata, Rhizophora stylosa, Sonneratia alba and Heritiera littoralis. Analysis of community structure of mangroves showed the following results: Average stand basal area was 29.4 m2/ha total stems per hectare 797, Avicennia marina has the highest relative density of 46.68 percent and occurred frequently with 30 percent making it also the most important species with an importance value of 835.1. Avicennia marina also dominated the area with a relative dominance of 39.44 percent. The area was observed to be recovering having a seedling density of 42.89 percent represented by Lumnitzera racemosa. The area has a diversity index of 0.73 and distribution of individual of various species is evenly distributed. Physico-chemical factors seemingly influenced the mangrove community structure in this area.